THE EFFECT of INTELLECTUAL CAPITAL, INDEPENDENT COMMISSIONERS, AND AUDIT COMMITTEE on FIRM VALUE - Dyah Aruning Puspita; Devi Ayuningtyas; Sugeng Hariadi (Jurnal Penelitian Ekonomi dan Akuntansi (JPENSI), 2023)
The purpose of this study is to examine the effect of intellectual capital, independent commissioner, and audit committee on company value in food and beverage sub sector companies listed on the Indonesia Stock Exchange (IDX) for 2019-2021. The independent variable in this study are intellectual capital, independent commissioner, and audit committee. The dependent variable is firm value as measured by Price Book Value (PBV). The population used ih this research is the food and beverage sub sector companies listed on the IDX for 2019-2021, the sample was taken using the purposive sampling method with a total of 36 samples. The method used is this research is multiple linear regression test. This type of research is quantitative using the Statistical Program for Social Science (SPSS). The results of this study indicate that intellectual capital has a significant effect on firm value, while independent commissioner and audit committee have no significant effect on firm value.